Fatigue damage model and parameter estimation of cemented sand and gravel material under cyclic loading. Issue 26 (26th October 2022) - Zhang, Xiancai; Huang, Hu; Li, Po
Abstract: Based on the stress-strain relationship under cyclic loading by large dynamic triaxial test, the cumulative strain distribution law of CSG materials was studied, and a dynamic damage model of CSG material was established by determining reasonable dynamic damage variables, the physical meaning and the values range for CSG material of this mode parameters were studied, too. The results show that the relationship curve between damage variable and cycle number of CSG material under cyclic loading is inverted S-type, which can be divided into three stages, and similar to the distribution law of cumulative strain. The three stages are corresponding to the closure of original defects, the initiation and propagation of new cracks, and the unstable propagation. According to the value of the damage development factors of the CSG material in the damage model, the fatigue life of CSG material under cyclic loading can be determined.